Understanding viruses and viral infections by biophotonic methods. Issue 1 (5th February 2022) - Ramoji, Anuradha; Pahlow, Susanne; Pistiki, Aikaterini; Rueger, Jan; Shaik, Tanveer Ahmed; Shen, Haodong; Wichmann, Christina; Krafft, Christoph; Popp, Juergen
Abstract: In the last few decades outbreaks of viral infections have often challenged the world‐wide health infrastructure and caused a significant financial burden as well as human suffering despite progress in diagnostic technologies. The recent outbreaks of the Ebola virus in the African continent, the Zika virus in the American continent, severe acute respiratory syndrome (SARS), Middle East respiratory syndrome (MERS), influenza A and lately severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) viral infections have repeatedly highlighted the importance of technological advancement enabling a better understanding of virions. In this review, we systematically discuss different aspects of virions and how their properties and functions can be studied using different light‐based technologies. We focus on virion classification, detection and interactions with the host's immune system. Further, the potential of advanced biophotonic methods, for example, Raman, infrared reflection, absorption and fluorescence spectroscopy, advanced microscopic techniques and biosensor‐based approaches for diagnosing viral infections, investigating therapeutics and vaccine development are described. Although significant advancements have already been made in photonic technologies, which even enable visualizing virion‐host interactions on single‐cell level, the continuous evolution of viruses demands further progress in biophotonic solutions for fast, affordable and robust health monitoring devices for screening viral infections. Abstract :